2016
DOI: 10.1186/s13048-016-0213-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide transcriptional regulation of estrogen receptor targets in fallopian tube cells and the role of selective estrogen receptor modulators

Abstract: BackgroundThe fallopian tube epithelium is one of the potential sources of high-grade serous ovarian cancer (HGSC). The use of estrogen only hormone replacement therapy increases ovarian cancer (OVCA) risk. Despite estrogen’s influence in OVCA, selective estrogen receptor modulators (SERMs) typically demonstrate only a 20 % response rate. This low response could be due to a variety of factors including the loss of estrogen receptor signaling or the role of estrogen in different potential cell types of origin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…The ovary produces a large number of hormones and growth factors that may stimulate migration of tumorigenic FTE cells to the ovaries. Estradiol is a major ovarian hormone, but it had no effect on migration of MOE cells [39]. In addition, steroids circulate systemically, making it unlikely that they stimulate the local migratory step from the fallopian tube to the ovary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ovary produces a large number of hormones and growth factors that may stimulate migration of tumorigenic FTE cells to the ovaries. Estradiol is a major ovarian hormone, but it had no effect on migration of MOE cells [39]. In addition, steroids circulate systemically, making it unlikely that they stimulate the local migratory step from the fallopian tube to the ovary.…”
Section: Discussionmentioning
confidence: 99%
“…The next day the media was replaced with serum free MEM. Twenty-four hours later, media with appropriate treatments were added to each well and cell lysates were collected at indicated times in RIPA buffer containing protease and phosphatase inhibitors [39]. Protein concentrations were determined with a BCA assay (23227, Thermo Scientific, Waltham, MA), and 25 µg of protein was separated in a 10% SDS-PAGE gel by applying constant voltage (100 V) for 120 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Preclinical studies have shown that estrogens can promote the proliferation of ovarian cancer cells lines and fuel tumor growth in mouse xenograft models [14], which is partly blocked by antiestrogens. Therefore, the use of endocrine disrupting agents in HGSOC could be promising [15]. Indeed, treatment of women with recurrent HGSOC using the antiestrogen tamoxifen or the aromatase inhibitor letrozole resulted in response rates between 10% and 15% and disease stabilization rates of 30% to 40% [16].…”
Section: Introductionmentioning
confidence: 99%
“…Recent use of unbiased genomic and proteomics approaches demonstrate that both OSE and FTE are capable of giving rise to epithelial ovarian cancer [ 5 , 6 ]. Since our lab showed that prolonged E2 exposure impacts both cell types and genome-wide transcriptional regulation of estrogen receptor targets in mouse FTE was recently investigated [ 7 ], we present the transcription dynamics of estrogen-induced dysplasia in primary cultures of mouse OSE to further advance our understanding of how estrogen can accelerate transformation from either cells of origin.…”
Section: Introductionmentioning
confidence: 99%